3D-CFD Simulation of Liquid–Liquid Two-Phase Flow in A Pilot-Plant Scale Annular Pulsed Disc and Doughnut Column. Issue 5 (29th July 2018) - Yu, Xiong; Zhou, Han; Jing, Shan; Lan, Wenjie; Li, Shaowei
ABSTRACT: A three-dimensional (3D) computational fluid dynamics (CFD) simulation of liquid–liquid two-phase flow is performed on a pilot-plant scale annular pulsed disc and doughnut column (APDDC). Two-fluid Euler–Euler method augmented with k-ε model is used. The two-phase hydraulic performance are investigated and compared with experimental results under various operation conditions. Favorable agreements are obtained, corroborating the ability of the simulation model to predict hydrodynamic parameters of pilot-plant scale APDDC. As a novel result, it is discovered that circumferential fluctuations of continuous phase velocity and dispersed phase volume fraction exist in the pilot-plant scale APDDC, which might be due to the large-scale structure of turbulence. Effects of operation conditions on the hydrodynamic performance and flow profiles in APDDC are studied based on simulation results and correlated regarding to operation parameters. The studied hydrodynamic parameters include turbulent kinetic energy dissipation, swirling strength, and pressure drop.